Analysing the Effect of Humidity and Rain on LoRa Signal Performance - Hasli, Nur Fakhira Nabila; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2026)
This project attempts to analyse the effects of humidity and rain on LoRa (Long-Range) signal performance. The range of the LoRa signal influenced by humidity and rain is considered for outdoor conditions up to 10 meters. The experimental design includes two Arduino Uno boards: the transmitter node connected to the DHT22 sensor for measuring humidity and rain, while the receiver node incorporates the LoRa SX1278 to measure the RSSI and SNR values. In dry conditions (humidity of 73-74%), the RSSI values measured -114 to -121 dBm at 1 to 4 meters. In moderate rain conditions (rain intensity of 70-95%), the RSSI values were within -115 to -121 dBm at 1 to 6 meters. In heavy rain conditions (rain intensity of 99-100% at a humidity level of 91-94%), the RSSI values steadily indicated -115 to -121 dBm at 1 to 10 meters. The experiment indicates that the signal became weak due to intense weather conditions while maintaining a stable range.